1994
DOI: 10.1016/0014-5793(94)00699-7
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐like peptide 1: A potent glycogenic hormone

Abstract: GLP-1(7-36)amide is an insulinotropic peptide derived from the intestinal post-translational proglucagon process, the release of which is increased mainly after a carbohydrate meal; also, its anti-diabetogenic effect in normal and diabetic states has been reported. In this study, GLP-1(7-36)amide stimulates the formation of glycogen from glucose in isolated rat hepatocytes, such a glycogenic effect being achieved with physiological concentrations of the peptide. The GLP-1(7-36)amide-induced glycogenesis is abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(57 citation statements)
references
References 17 publications
3
54
0
Order By: Relevance
“…This led us to postulate that in insulin-resistant states (e.g., aging), we see insulinomimetic properties of GLP-1 that we did not appreciate in an earlier study of young lean subjects where glucose uptake was normal (11). In another model of insulin resistance, obese subjects with a BMI of Ͼ30 kg/m 2 , we found that GLP-1 infusions increased glucose uptake by 25% above that due to insulin alone (19).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…This led us to postulate that in insulin-resistant states (e.g., aging), we see insulinomimetic properties of GLP-1 that we did not appreciate in an earlier study of young lean subjects where glucose uptake was normal (11). In another model of insulin resistance, obese subjects with a BMI of Ͼ30 kg/m 2 , we found that GLP-1 infusions increased glucose uptake by 25% above that due to insulin alone (19).…”
mentioning
confidence: 64%
“…Plasma levels of GLP-1 increase after eating, and it has already been shown that GLP-1 augments insulin secretion in response to meals. In vitro studies have found that GLP-1 augments insulin-mediated glucose uptake (1)(2)(3)(4)(5)(6)(7), but the results of in vivo studies are conflicting (8 -15). The exogenous administration of GLP-1 lowers blood glucose levels in both type 1 and type 2 diabetic subjects (9,(11)(12)(13)(14)16).…”
mentioning
confidence: 99%
“…Further metabolic properties of GLP-1 include peripheral effects such as inhibition of feeding (Turton et al 1996) and reduction of gastrointestinal motility and secretion (Wettergren et al 1993). Glycogenic effects of GLP-1 in liver, skeletal muscle and abdominal muscle (Valverde et al 1994, O'Harte et al 1997 and lipogenic effects in adipose tissue (Oben et al 1991, Perea et al 1997 have also been reported, although there is no reproducible evidence that a GLP-1 receptor exists in these tissues (Bullock et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, administration of the GLP-1r antagonist to block hepatic GLP-1 signalling results in glucose intolerance [31]. In vitro study in cultured rat hepatocyte has showed that GLP-1 promotes glycogen accumulation by increasing the activity of glycogen synthase-A while decreasing the activity of glycogen phosphorylase-A [32]. Whether the GLP-1 acts directly on hepatocytes or indirectly through neuronal networks remains to be determined.…”
Section: Glp-1mentioning
confidence: 98%
“…Circulating GLP-1 has two forms, GLP and GLP [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] amide. About 80% of circulating GLP1 in human is GLP [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] amide [18]. Plasma levels of GLP-1 in the basal level range between 5-10 pM and its level could increase to 50 pM after a meal.…”
Section: Glp-1mentioning
confidence: 99%